Toward large-scale fabrication of triboelectric nanogenerator (TENG) with silk-fibroin patches film via spray-coating process. (November 2017) - Liu, Chaoran; Li, Jiaqian; Che, Lufeng; Chen, Shaoqiang; Wang, Zuankai; Zhou, Xiaofeng
Abstract: Over the past several years, the development of triboelectric nanogenerator (TENG) has blossomed owing to many advantages such as the simple structure, high conversion efficiency and wide material selectivity. Currently, most of TENG devices are constructed with micro-structured surfaces using complicated manufacturing processes. Owing to the lack of high-volume manufacturing scalability, it still remains a bottleneck to apply TENG into the commercial products. In this work, we report the development of a novel TENG, which leverages on the regenerated, flexible, biocompatible, and highly transparent silk-fibroin as a triboelectric layer and can be deposited on a PET/ITO substrate (SF/PET/ITO) using a simple spray-coating process. The as-fabricated TENG exhibits a maximum voltage of 213.9 V and a high power density of 68.0 mW/m 2 as a result of the ability of losing electrons and rough surface rendered by the silk-fibroin. We further demonstrate that this generator can charge a capacitor (10 μF) to 4.5 V in 6 mins, and instantaneously light up as many as 100 commercial LED bulbs. We anticipate that the large-scale fabrication of silk-fibroin-based TENGs will serve as a promising system for electricity generation with an extremely low cost to commercial applications. Graphical abstract: Highlights: Spray-coating process brings an efficiency, large-scale, high throughput and low-cost technique for TENGs fabrication. The silk fibroin patches film prepared by simple spray-coating has been applied in TENGs fabrication. TENG with silk-fibroin patches demonstrates excellent output performance and extraordinary optical transmittance. A new insight in extending the design of TENGs to the commercialized applications of energy harvesting.